Topical Diclofenac Reprograms Metabolism and Immune Cell Infiltration in Actinic Keratosis - Singer, Katrin; Dettmer, Katja; Unger, Petra; Schönhammer, Gabriele; Renner, Kathrin; Peter, Katrin; Siska, Peter J.; Berneburg, Mark; Herr, Wolfgang; Oefner, Peter J.; Karrer, Sigrid; Kreutz, Marina; et al. (Frontiers in Oncology, 2019)
Background: Melanoma and squamous cell carcinoma of the skin are characterized by an altered glucose metabolism, but little is known about metabolic changes in precancerous skin lesions such as actinic keratosis (AK). Here, we studied the central carbon metabolism and immune cell infiltrate of actinic keratosis lesions before, under, and 4 weeks after treatment with topical diclofenac (Solaraze®). Methods: This study was designed as a prospective, randomized, controlled, monocentric investigation (ClinicalTrials.gov Identifier: NCT01935531). Myeloid and T cell infiltration was analyzed in skin biopsies from 28 patients by immunohistochemistry. Furthermore, immune cell activation was determined via quantitative real-time PCR (IFN-g, IL-10, CSF1, TGF-b, IL-6). Glucose, amino acid and Krebs’ cycle metabolism was studied by mass spectrometry prior, during and after treatment with topical diclofenac. Biopsies from sun-exposed, untreated, healthy skin served as controls. Results: Increased lactate and decreased glucose levels suggested accelerated glycolysis in pre-treatment AK. Further, levels of Krebs’ cycle intermediates other than citrate and amino acids were elevated. Analysis of the immune infiltrate revealed less epidermal CD1a+ cells but increased frequencies of dermal CD8+ T cells in AK. Treatment with diclofenac reduced lactate and amino acid levels in AK, especially in responding lesions, and induced an infiltration of dermal CD8+ T cells accompanied by high IFN-g mRNA expression, suggesting improved T cell function. Discussion: Our study clearly demonstrated that not only cancers but also pre-malignant skin lesions, like AK, exhibit profound changes in metabolism, correlating with an altered immune infiltrate. Diclofenac normalizes metabolism, immune cell infiltration and function in AK lesions, suggesting a novel mechanism of action.